Are Fibular Allograft Struts Useful for Unicameral Bone Cysts of the Proximal Humerus in Skeletally Mature Patients?. Issue 6 (14th June 2022) - Jamshidi, Khodamorad; Bahradadi, Mehrdad; Bahrabadi, Marjan; Mirzaei, Alireza
Abstract: Background: Although most unicameral bone cysts (UBCs) are either successfully treated or have healed by the time of skeletal maturity, a small proportion of patients will have persistent UBCs beyond the age of skeletal maturity. More reliable methods are needed to treat persistent UBCs in the humerus because these cysts are associated with a high risk of fracture due to thinning of the humeral cortex. In this study, we evaluated whether inserting a fibular strut allograft into the humerus would be associated with healing of the cyst and union of associated pathologic fractures in skeletally mature patients with a UBC of the proximal humerus. Questions/purposes: (1) How effective is inserting a fibular strut allograft in the healing of proximal humerus UBCs in skeletally mature patients with bone cysts and associated fractures? (2) What are the functional results of this procedure? (3) What complications are associated with this procedure? Methods: Between 2005 and 2018, we surgically treated 23 skeletally mature patients with persistent humeral UBCs and any of the following indications: a progressive cyst that was not responsive to aspiration and 2 to 3 steroid injections, a cyst with a pathologic fracture, and a cyst at high risk of fracture. Of those, patients with a cyst located in the proximal humerus and a defect length more than 6 cm (n = 18) were considered eligible to be treated with insertion of a fibular strut allograft through a hole created in the greater tuberosity. A further two patients were excluded because they were treated by other surgical methods. From the remaining 16 patients, two patients were lost to follow-up before 2 years and could not be analyzed in this study. Another two patients had incomplete datasets, leaving 12 for analyses in this retrospective study. Three patients presented with a pathologic fracture. Complete filling of the cysts with bone within 24 months was regarded as healing, and after 24 months it was classified as delayed healing. Cyst consolidation with small residual areas of osteolysis was considered healed with residual radiographic appearance. Fracture union was determined by the clear observation of at least three of four cortical views bridged by bone in the radiographic follow-up 3 months after the operation. Fractures in which the cortices were not bridged by bone after 3 months were regarded as a delayed union. The functional outcome of the patients was assessed by the Musculoskeletal Tumor Society (MSTS) scoring system, with a total score ranging from 0 to 30. A higher score was indicative of less pain and better function. MSTS scores were obtained through a chart review by an orthopaedist who was not involved in the care administered. Results: At a median (range) follow-up of 57 months (33 to 87), the cyst was completely healed in nine patients and healed with residual cyst in the remaining three. Union was observed within 3 months in all patients who presented with a pathologic fracture. The median MSTS score of the patients was 30 (28 to 30). No postoperative complications such as persistent pain or re-fracture were observed. Conclusion: The primary goal of treating a UBC of the proximal humerus is to prevent fracture of the affected bone; insertion of a fibular strut graft in this study met this goal. Therefore, we believe a fibular strut allograft insertion is worth consideration when treating proximal humeral UBCs in skeletally mature patients. Further studies will be needed to determine whether this approach has benefits compared with other treatment options. Level of Evidence: Level IV, therapeutic study.